Preparation, characterization, and in vitro antibacterial activity of Cu(II)-pyrazinamide complexes, - Galuh Wahyu Karti'a; Danar Purwonugroho; Arie Srihardyastutie; Yuniar Ponco Prananto (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2024)
Transition metal complexes, including copper(II) complexes, are being investigated as potential next-generation antibacterial agents. This study aims to prepare several Cu(II)-pyrazinamide (Cu(II)-pza) complexes using Cu(II) salts (acetate, chloride, nitrate, sulphate) through a direct mixing technique. Different Cu(II) salts are anticipated to yield distinct complexes, resulting in varied antibacterial properties. The Cu(II)-pza complexes were characterized using melting point analysis, infrared spectroscopy, and powder X-ray diffraction (XRD). Melting point analysis provides insights into the physical properties of the complexes. Infrared spectroscopy identifies functional groups and predicts chemical bonds within the complexes. Powder XRD analyzes the characteristic diffraction patterns of the complexes. Experimental data reveal that the infrared spectra of all Cu(II)-pza complexes exhibit typical absorption bands of the pyrazinamide ligand (N-H, C=O, C-N, and C=N). Powder XRD analysis shows different diffraction patterns for each complex, indicating the formation of different compounds due to variations in anion and metal-ligand interactions, with the sulphate complex matching a previously reported complex. Melting point tests indicate the decomposition of the complexes within the range of 215–225 °C, except for the acetate complex, which decomposes at 275 °C. The antibacterial activities of these complexes against S. aureus and E. coli were examined in vitro based on inhibition zone diameter and MIC value. The sulphate, nitrate, and chloride complexes exhibit MIC values of 1,000 ppm and MBC values of 6,000 ppm, demonstrating better antibacterial activity against S. aureus than E. coli. These findings suggest the potential of Cu(II)-pza complexes as antibacterial agents. Further studies, such as crystal structure determination, are necessary to explore the possible mechanisms of antibacterial activity.[1] N. C. Handayani, A. Kusuma, R. Purwanto, R. E. Prasetya, and A. Budiman, “Pengembangan Agen Potensi Pengembangan Agen Antibakteri dari Senyawa Kompleks Logam Transisi di Indonesia,” The Indonesian Green Technology Journal, vol. 10, no. 1, pp. 9-20, 2021.[2] R. S. Hellberg and E. Chu, “Effects of climate change on the persistence and dispersal of foodborne bacterial pathogens in the outdoor environment: A review,” Crit. Rev. Microbiol., vol. 42, no. 4, pp. 548–572, 2016. doi: 10.3109/1040841X.2014.967385.[3] T. Li, Y. Wang, X. Zhang, J. Chen, and L. Sun, “Bacterial resistance to antibacterial agents: Mechanisms, control strategies, and implications for global health,” Sci. Total Environ., vol. 860, p. 160148, 2023. doi: 10.1016/j.scitotenv.2022.160148.[4] N. A. Church and J. L. McKillip, “Antibiotic resistance crisis: challenges and imperatives,” Biologia (Bratisl)., vol. 76, no. 5, pp. 1535–1550, 2021. doi: 10.2478/s11756-021-00707-5.[5] World Health Organization,